Analisis Strategi Guru Dalam Memaksimalkan Sarana Prasarana Pembelajaran Di Kelas 5 SDN 2 Cikancra - Ihsan Alfa Rasid; H. Dudung Suryana; Fajar Nugraha (LPPM Politeknik Pratama, 2023)
The teacher is a professional educator who educates, evaluates students. This study aims to determine (1) The management of learning infrastructure facilities at SDN 2 Cikancra, (2) The teacher's strategy in maximizing the available learning infrastructure and overcoming the limitations of infrastructure facilities in the learning process in grade 5 SDN 2 Cikancra. This research uses a qualitative approach with descriptive methods. The type of data used is primary data. The data collection techniques used are through observation, interview and documentation techniques. After the data is collected, then describe the data obtained in accordance with the facts that occur in the field. Based on the results of the study, it is suggested that the availability of learning infrastructure facilities in class V SDN 2 Cikancra has a percentage of 70.6% including in the good category, while for its condition it has a percentage of 88.2% including in the very good category. This is inseparable from the management of infrastructure facilities carried out by the SDN 2 Cikancra school which includes planning, procurement, utilization, maintenance, and elimination. The teacher's strategy in maximizing learning infrastructure facilities in Class 5 SDN 2 Cikancra can be categorized as good, because the teacher uses multifunctional infrastructure facilities, it aims to cover unavailable and damaged infrastructure facilities.